Do Firm and Board Characteristics Affect Carbon Emission Disclosures? - Saraswati, Erwin; Puspita, Nadia Rani; Sagitaputri, Ananda (International Journal of Energy Economics and Policy, 2021)
This research examines how profitability, company size, board independence, and board gender diversity affect carbon emission disclosures in Indonesian companies. The sample of this study consists of 36 manufacturing companies which were consecutively listed on Indonesian Stock Exchange from 2015 to 2018. The carbon emission disclosures were measured using a disclosure checklist consisting of 18 items. Using multiple regression analysis, this study found that carbon emission disclosures are greater in more profitable and larger companies. This suggests that financial resources availability and the political visibility can increase carbon emission disclosures. This study also finds that carbon emission disclosures are greater in companies with a large portion of independent commissioners and female directors. This supports the legitimacy and stakeholder theories that a more independent and diversified board will be more able to manage different stakeholder expectations. The findings can provide evidence to companies about how to increase their carbon emission disclosures, which can consequently help the government to control the national carbon emissions. Keywords: carbon emission disclosure, profitability, company size, board independence, board gender diversity JEL Classifications: Q56, G34, M14 DOI: https://doi.org/10.32479/ijeep.10792